International Financial Statistics, June 2016. (International Financial Statistics; International Financial Statistics ;, 2016)
The June 2016 issue of International Financial Statistics (IFS) is a standard source of statistics on all aspects of international and domestic finance. IFS publishes, for most countries of the world, current data on exchange rates, international liquidity, international banking, money and banking, interest rates, prices, production, international transactions (including balance of payments and international investment position), government finance, and national accounts. The country table notes in the monthly issues identify the exchange rates used. Quotas are reviewed at intervals of not more than five years. The reviews take account of changes in the relative economic positions of members and the growth of the world economy. The IMF normally determines the currencies that are used in transactions and operations with members. Each quarter, the IMF prepares a financial transactions plan, in which it indicates the amounts of currencies and SDRs to be used during the relevant period.